2014
DOI: 10.1128/jvi.01801-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cellular Tropism of Gorilla Simian Foamy Virus in Blood of Infected Humans

Abstract: Simian foamy viruses (SFV) are retroviruses that are widespread among nonhuman primates. SFV can be transmitted to humans, giving rise to a persistent infection. Only a few data are available concerning the distribution of SFV in human blood cells. Here we purified blood mononuclear cell subsets from 11 individuals infected with a Gorilla gorilla SFV strain and quantified SFV DNA levels by quantitative PCR. SFV DNA was detected in the majority of the CD8 ؉ , CD4 ؉ T cells were positively correlated with the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…ϩ T, and B lymphocytes in the blood of infected humans (30). Our study also revealed natural polymorphisms in gag and bet between SFV strains originating from different chimpanzee subspecies and polymorphisms in U3 and tas at the interindividual level (31).…”
mentioning
confidence: 73%
“…ϩ T, and B lymphocytes in the blood of infected humans (30). Our study also revealed natural polymorphisms in gag and bet between SFV strains originating from different chimpanzee subspecies and polymorphisms in U3 and tas at the interindividual level (31).…”
mentioning
confidence: 73%
“…By studying a larger cohort of humans infected with a gorilla strain of SFV in Cameroon, we demonstrated that CD8+, CD4+ T cells and CD19+ B lymphocytes were preferentially infected, compared to monocytes and NK cells ( Table 1). SFV DNA was detected in both memory and naive CD4+ T lymphocytes and SFV DNA levels in CD4+ T cells were positively correlated with the duration of the infection [27].…”
Section: Sfv Tropismmentioning
confidence: 94%
“…Porcine circovirus type 2 (PCV2) spliced capsid mRNA (Cap mRNA) and viral DNA were detected in B lymphocytes from pigs, although no further studies were performed to determine if the presence of these nucleic acids corresponds to a productive infection, with release of viral progeny from these cells (20). The capacity of simian foamy viruses (SFVs) to transcribe genes in human B lymphocytes was also recently described (21). Interestingly, live rabies virus vaccines have been shown to infect murine and human B lymphocytes (22).…”
mentioning
confidence: 99%